Dampak Potensial Perubahan Iklim Terhadap Dinamika Penularan Penyakit DBD Di Kota Mataram - Nur Alvira Pascawati; Tri Baskoro Tunggul Satoto; Tri Wibawa; Roger Frutos; Sylvie Maguin (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2019)
Mataram City is an endemic area of DHF because cases are always found in 3 consecutive years with the number of cases that fluctuated and tended to increase. DHF is related to climate factors because of vector life, pathogen, behavior and the physiology of the human body is influenced by climate. The impact of climate change on the dynamics of dengue transmission in the city of Mataram is very important to study because it can be used as a basis for knowing the pattern of the occurrence of dengue cases related to temperature, humidity, rainfall and wind speed. This study used a retrospective cohort design from BMKG secondary climate data and dengue cases at the Mataram City Health Office in the last 5 years (2013-2017). Data were analyzed based on monthly and annual patterns assuming normal data distribution to be carried out correlation and regression tests with α = 0.05. The results showed that climatic elements such as: humidity, rainfall, and temperature had a strong enough influence on the incidence of DHF, but the wind speed was not related to the incidence of DHF in the city of Mataram. The linear regression equation model found was DBD Case = -439.403 + 5.809 * humidity (R2 = 18.9%) assuming all linear regression was fulfilled.This model can be used to assist in efforts to mitigate dengue transmission through the determination of the timing of implementation of prevention and the provision of infrastructure facilities for the DHF treatment.